ANALISIS PROSES MERGER PT BANK SYARIAH INDONESIA, TBK BESERTA SINERGI YANG DIHASILKAN - Jessica Renata; Tiffanny Laurenzia; Nanik Linawati; Irene Wijaya; Jorge (Universitas Sarjanawiyata Tamansiswa, 2026)
This research aims to analyze the merger process of three state-owned sharia banks, which are PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah Indonesia Tbk. This research focuses on the financial condition before and after the merger, the stages of the merger process, and organizational integration of the merger. A qualitative approach with an explanatory case study design was used. Secondary data were taken from the annual reports, general documents and news about the merger, Otoritas Jasa Keuangan (OJK), and valid government news related to the merger. The results showed that the merger followed systematic stages, starting from initiation, due diligence, the signing of the Conditional Merger Agreement, regulatory approval, extraordinary general meeting of shareholders, and post-merger integration. BSI’s financial performance improved after the merger, shown by an increase in ROA, a decline in BOPO, and growth in third-party funds. The merger also generated operational, market, cost, and technology synergies that strengthened BSI’s position in the sharia banking industry.